BLOCK PERIODIZATION – A BREAKTHROUGH OR A MISCONCEPTION - Vladimir Koprivica (SportLogia, 2012)
Block periodization emerged as a new idea in the preparation of athletes. Based on the analysis of the traditional theory of sports training and its segments and training periodization during the competitive season, the supporters of block periodization made a number of objections. The main conclusion was that classical periodization no longer meets the requirements of modern sports because of the extended competition calendar. Classical periodization is based on the simultaneous development of multiple abilities over a longer preparation period and large volumes of work. It prevents the athletes from participating successfully in several competitions during the season. However, according to the supporters of block periodization, this applies only to top athletes.On the other hand, there are many objections to the justification and logic of block periodization. The term “block periodization” is not adequate, and the criticism of the classical theory is methodologically incorrect because it refers to old bibliographic sources, (and) the opponents are not mentioned. It is not realistic in practice to work successively on more abilities because of short periods of preparation, there is not enough time to recover after such an effort while the risk of injury is significantly higher. Most importantly, according to the block periodization it is difficult to be fit at the right time, which is the main purpose of periodization. Therefore, one could rather say that block periodization is a misconception, rather than a breakthrough in training.